BMSCs and Osteoblast-Engineered ECM Synergetically Promotes Osteogenesis and Angiogenesis in an Ectopic Bone Formation Model - Zhang, Chi; Xia, Dongdong; Li, Jiajing; Zheng, Yanan; Weng, Bowen; Mao, Haijiao; Mei, Jing; Wu, Tao; Li, Mei; Zhao, Jiyuan (Frontiers in Bioengineering and Biotechnology, 2022)
Bone mesenchymal stem cells (BMSCs) have been extensively used in bone tissue engineering because of their potential to differentiate into multiple cells, secrete paracrine factors, and attenuate immune responses. Biomaterials are essential for the residence and activities of BMSCs after implantation in vivo. Recently, extracellular matrix (ECM) modification with a favorable regenerative microenvironment has been demonstrated to be a promising approach for cellular activities and bone regeneration. The aim of the present study was to evaluate the effects of BMSCs combined with cell-engineered ECM scaffolds on osteogenesis and angiogenesis in vivo. The ECM scaffolds were generated by osteoblasts on the small intestinal submucosa (SIS) under treatment with calcium (Ca)-enriched medium and icariin (Ic) after decellularization. In a mouse ectopic bone formation model, the SIS scaffolds were demonstrated to reduce the immune response and lower the levels of immune cells compared with those in the sham group. Ca/Ic-ECM modification inhibited the degradation of the SIS scaffolds in vivo. The generated Ca/Ic-SIS scaffolds ectopically promoted osteogenesis according to the results of micro-CT and histological staining. Moreover, BMSCs on Ca/Ic-SIS further increased the bone volume percentage (BV/TV) and bone density. Moreover, angiogenesis was also enhanced by the Ca/Ic-SIS scaffolds, resulting in the highest levels of neovascularization according to the data of CD31 staining. In conclusion, osteoblast-engineered ECM under directional induction is a promising strategy to modify biomaterials for osteogenesis and angiogenesis. BMSCs synergetically improve the properties of ECM constructs, which may contribute to the repair of large bone defects.